Sensor for diuron quantitation based on the P450 biomimetic catalyst nickel(II) 1,4,8,11,15,18,22,25-octabutoxy-29H,31H-phthalocyanine - Wong, Ademar [UNESP]; De Vasconcelos Lanza, Marcos Roberto; Sotomayor, Maria Del Pilar Taboada [UNESP] (Elsevier, 2013)
A biomimetic sensor based on a carbon paste electrode modified with the nickel(II) 1,4,8,11,15,18,22,25-octabutoxy-29H,31H-phthalocyanine complex was developed as a reliable alternative technique for the sensitive and selective analysis of the herbicide diuron in environmental media. The sensor was evaluated using cyclic voltammetry and amperometric techniques. The best amperometric responses were obtained at 750 mV vs. Ag/AgCl (KClsat), using 0.1 mol L-1 phosphate buffer solution at pH 8.0. Under these conditions, the sensor showed a linear response for diuron concentrations between 9.9 × 10-6 and 1.5 × 10-4 mol L -1, a sensitivity of 22817 (±261) μA L mol-1, and detection and quantification limits of 6.14 × 10-6 and 2 × 10-5 mol L-1, respectively. The presence of the nickel complex in the carbon paste improved selectivity, stability, and sensitivity (which increased 700%), compared to unmodified paste. The applicability of the sensor was demonstrated using enriched environmental samples (river water and soil). © 2012 Elsevier B.V. All rights reserved.
Keywords: Biomimetic sensor; Diuron; Nickel(II) 1,4,8,11,15,18,22,25- octabutoxy-29H,31H-phthalocyanine; P450 enzyme; A-carbon; Ag/AgCl; Amperometric; Amperometric response; Biomimetic catalysts; Biomimetic sensors; Carbon pastes; Detection and quantification limit; Environmental media; Environmental sample; Linear response; Nickel complex; Phosphate buffer solutions; Phthalocyanine complexes; River water; Selective analysis; Biomimetics; Carbon; Cyclic voltammetry; Nickel compounds; Sensors; Urea; Herbicides